A Service system study on Utility XYZ - Baligod, Robin; Librando, Zeerynah C.; Rigor, May M.; Sabareza, Ma. Genaline V. (Diliman, Quezon City College of Engineering, 1997)
Utility XYZ is a utility company that distributes electricity to the municipality of Tarlac. It is a family-corporaton that has been handed down from generation fo generation, they have been in operation for forty-eight years. Operating costs for Utility XYZ is high. Utility XYZ being a distributor sources electricity from Napocor. Electricity is bought from Napocor at a lower price and distributed at a higher price, the difference is profit and operating costs. If the operating costs are high the profit becomes smaller, so it is of consequential value to decrease operating costs to increase benefits. Part of the operation is the determination of the contract demand. The contract demand is the "contract" (or amount ) of electrical consumption of Utility XYZ for a given year. Penalties are imposed if Utility XYZ goes below or above the given contract demand. Presently penalties have reached millions in a month due to lack of adequate forecasting techniques. There is no existing inventory model for the equipment that Utility XYZ is currently using. This paper has discussed most operating problems and has cut down penalties by 100%. The problem areas addressed by the study are the following: Forecasting - The electrical consumption for the next five years was forecasted. Capacity Planning - determination of optimum annual contract demand for the next five years using forecasted electrical consumption and simulation. Inventory System - Fixed Order Quantity model was designed for Utility XYZ generating up to 32% of savings. Aggregate Planning - the procedure for determining the manpower requirements in the upgrading of wires and installation of meterboxes was laid out.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Electric utilities; Production engineering